Legal viable options to incessant closure of Nigeria's international borders. Issue 1 (2nd January 2023) - Omale, Musa Godwin; Olorunfemi, John Funsho; Aiyegbajeje, Femi Ola
ABSTRACT: Just like in 1984 and 2003 when Nigeria's borders were closed to the neighbouring countries, the closure of Nigeria's land border since August 2019 which is intended to combat smuggling of goods and to boost manufacturing and agricultural production has been subject of controversy. This paper observes that although the border closure may have brought some advantages in the area of increased revenue, numerous seizures of illegal materials and encourages local production of rice, the appraisal of the legal, economic, political and security implications however reveal that despite the perceived advantages, it may not be the best option. It concedes that the closure of the Nigerian borders is an exercise within its sovereign authority; but however, notes that the effect of an arbitrary border closure without sufficient notice adversely affects the interests of genuine businessmen as this amounts to a breach of their fundamental right of doing legitimate business across the border. It recommends viable legal options which the government can explore in line with standard global practice such as systemic efforts to boost the economy, by ensuring effective control, management, monitoring and protection of the border. It calls for regional integration and less burdensome procedures without undermining national interests.